2020
DOI: 10.3390/molecules25163614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Time and Temperature on Antioxidants in Juice from Momordica charantia L. and Momordica charantia L. var. abbreviata Ser.

Abstract: This study determined the antioxidant activities of juice from Momordica charantia L. (MC) and MC var. abbreviata Ser. (MCVAS) by analyzing 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging ability, ferric reducing power (FRP), and total phenolic content (TPC). The effects of storage time and storage temperature on these antioxidant activities were investigated. Liquid chromatography–mass spectrometry was conducted to identify the major components of MC and MCVAS. The results revealed that the antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…A published protocol [36,37] was employed with some modifications. In brief, 100 μL of 2 mM PBS buffer (pH 6.6), 100 μL of 1% potassium ferricyanide (K 3 Fe(CN) 6 ), and 100 μL of the by-product extract were evenly mixed in a 50 °C water bath for 20 minutes.…”
Section: Reductive Capacity Testmentioning
confidence: 99%
“…A published protocol [36,37] was employed with some modifications. In brief, 100 μL of 2 mM PBS buffer (pH 6.6), 100 μL of 1% potassium ferricyanide (K 3 Fe(CN) 6 ), and 100 μL of the by-product extract were evenly mixed in a 50 °C water bath for 20 minutes.…”
Section: Reductive Capacity Testmentioning
confidence: 99%
“…A major disadvantage of using plant material is the high variability in chemical composition and antioxidant properties, which depends not only on the changing environmental conditions, but also on the time of harvest, as well as storage and transport conditions [20,[80][81][82]. If we consider polyphenolic fractions as a source of antioxidants in the skin layers, it is important to estimate "competition" and "enhancer" properties of chemicals [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The favorable effects of bitter gourd come from chemical components including cucurbitane-type triterpenoids, cucurbitane-type triterpene glycoside, phenolic acids, flavonoids, essential oils, fatty acids, amino acids, sterols, saponin constituents, and proteins. The pulp of this plant has a higher antioxidant activity than that of the seeds, which may be attributed to the different extents of phenolic acids and flavonoids [ 102 ]. Current studies have confirmed that bitter gourd has the therapeutic potential of lowering blood sugar, and lowering blood lipids, as well as anti-inflammatory, antioxidant, and anti-carcinogenic effects [ 103 , 104 , 105 ].…”
Section: Momordica Charantia Lmentioning
confidence: 99%
“…As a rule, immature bitter melon with darker green skin is more bitter, while bitter melon with lighter skin is less bitter. Furthermore, WBM has much higher saponins than bitter melon [ 102 ].…”
Section: Momordica Charantia L Varmentioning
confidence: 99%